Wolność religijna i poprawność polityczna. - Aleksiejuk, Ks. Artur (Elpis, 2014)
We live in times that are particularly sensitive to issues such as freedom and are differentiated by strong aspirations for personal and societal freedom. One speaks of political-societal freedom, freedom of religion, artistic freedom and freedom to choose one’s own lifestyle. It would be possible to make a long list of the various kinds or manifestations of freedom, which modern individuals indentify in their lives. My essay considers the ways the law functions in regards to religious freedom in the context of the currently prevailing and implemented political visions in United Europe. Strictly speaking, this paper concerns the definition of place, which was assigned for religious convictions of citizens of the European Union and their role in shaping their personal and societal lives.